The Effectiveness of the 7E Learning Cycle Model Aided by Montessori Media on Students' Critical Thinking Ability - Syva Lestiyani Dewi; Muh Husen Arifin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this study was to determine the relationship between the Learning Cycle 7E learning model assisted by Montessori media on the critical thinking skills of elementary school students in class IV hearing senses. This research is motivated by the existence of a phenomenon where students have difficulty understanding material about the sense of hearing which is quite complicated because of the many terms used. Science subjects in elementary schools are generally taught by lecture and assignment methods, this will make students feel bored faster in class and unable to absorb the information conveyed correctly. Therefore, research was made to show how effective the Learning Cycle 7E model assisted by Montessori media was on students' critical thinking skills. This research was conducted using a quantitative approach with quasi-experimental methods. The research design developed was a quasi-experimental design model with nonequivalent control group design. The sample used was fourth grade students at SDN Sukarasa. As for the data processing techniques, the authors use descriptive techniques to obtain conclusions from this study. As a result, there is a positive relationship from the Montessori media-assisted LC 7E learning model to students' critical thinking skills. This is also supported by the opinions of experts on how effective learning can be done, one of which is by using a fun learning model so that children's thinking abilities increase.